Affective Profiles in a Massive Open Online Course and Their Relationship with Engagement - Tze, Virginia M. C.; Daniels, Lia M.; Buhr, Erin; Le, Lily (Frontiers in Education, 2017)
The importance of affect in learning has been firmly established in face-to-face learning environments and now researchers are examining the roles of affect in online learning environments, including massive open online courses (MOOCs). The purpose of this research was to identify profiles of common achievement emotions (i.e., relief, anxiety, boredom, and guilt) over the duration of one MOOC and examine the differences in academic engagement. Results from the Latent Profile Analysis revealed unique affective profiles, and these profiles differed significantly in cognitive, behavioural and social engagement in the MOOC. Our findings therefore highlight the importance of understanding affective profiles in MOOCs and address potential difficulties to engage these learners with a vast diversity in backgrounds.